Customers’ Perception on Service Quality in Commercial Records Centre - Farik Mat Yatin, Saiful; Hussin, Nurussobah; Zairul Masron, Mohd; Bee Wah, Yap; Ibrahim, Nurulhuda; Mizan Taib, Khairul; Razilan Abd Kadir, Mohd (International Journal of Engineering and Technology, 2018)
Service quality and customer satisfaction were important elements that businesses need to consider and to ensure they keep on competitive in their business. There is a need to measure these dimensions and to know how it effect the consumers’ perceptions for better understanding of their needs and hence giving the best service to satisfy them. It is important for the Commercial Records Centre (CRC) to have a good service quality in order to sustain their loyalty of their customers. It is very crucial for CRC to evaluate the performance of their services rendered to their customers, due to the fact that satisfied customers in most cases are likely to become loyal to companies. Thus, the aim of this case study is to determine customers’ perceptions on the service quality in one of the CRC in Shah Alam, Selangor Malaysia. Quantitative method is used to conduct the survey. Modified SERVQUAL questionnaire with the requirement standard from MS ISO 11799 (2011), Information and Documentation - Document Storage Requirements for Archive and Library Materials were used to assess the CRC customers or respondents’ perceptions of service quality according to five quality dimensions. From the findings, the most important factor that their customers emphasis from the most important to the least important was Assurance, Reliability, Tangibility, Responsiveness, Empathy. It is proven that, customers’ perception has a relationship or influence with five dimensions in SERVQUAL Model. This is only one finding of a case study. Different CRC will definitely have different findings from the customers perception.